Virtual Environment for Root Canal Modeling - Bogoni, Tales Nereu; Pinho, Márcio Sarroglia (Proceedings of the Brazilian Symposium on Computing Applied to Health (SBCAS), 2014)
This paper presents a simulator based on Virtual Reality equiped with a custom haptic device that allows the simulation of movements with endodontic files. Through an experiment tested by users with experience in endodontics has been proven that the method is effective at identifying errors on the sequence of instrumentation.